IMPLEMENTASI MODEL PEMBELAJARAN INQUIRY TRAINING DALAM PEMBELAJARAN FISIKA UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR FORMAL SISWA (Jurnal Pendidikan Fisika Indonesia, 2015)
Low ability of formal thinking students caused the learning outcomes they get too low. This study aims to determine the effectiveness of the inquiry learning model training in improving students' ability to think formal. The design was used quasi-experimental "non-equivalent groups pretest-posttest design". Implementation  experimental class learning with inquiry learning model training, control class learning with direct instruction. Data obtained through a formal thinking ability test thinking ability. Learning model efectivity in improving formal thinking ability is determined based on the gain score average which normalized by average difference test of statistic, namely t test. The results of the reasearch found that the inquiry training learning model is more effective in improving students formal thinking ability compared with the direct instruction learning model. The N-gain percentage of formal thinking ability of students in the experiment class in the indicators of hypothetical deductive thinking, combination thinking and reflection thinking are in the medium category, just proportional thinking is the high category. N-gain average percentage of control class for the hypothesis deductive thinking is just in the low category, while the proportional thinking, combination thinking and reflection thinking are in the medium category.Rendahnya kemampuan berpikir formal siswa menyebabkan hasil belajar yang mereka peroleh juga rendah. Penelitian ini bertujuan untuk mengetahui efektivitas  model pembelajaran inquiry training dalam meningkatkan kemampuan berpikir formal  siswa. Disain yang digunakan adalah kuasi eksperimen “non-equivalent groups pretest-posttest design”. Implementasi pembelajaran kelas eksperimen dibelajarkan dengan model pembelajaran inquiry training, kelas kontrol dengan model pembelajaran direct instruction.  Data kemampuan berpikir formal diperoleh melalui tes kemampuan berpikir formal. Efektivitas  model pembelajaran  dalam meningkatkan kemampuan berpikir formal ditentukan berdasarkan rerata skor gain yang dinormalisasi dengan statistik uji beda rerata, uji t.  Hasil penelitian ditemukan bahwa pembelajaran dengan model inquiry training lebih efektif dalam meningkatkan kemampuan berpikir formal siswa dibandingkan dengan pembelajaran direct instruction. Persentase N-gain kemampuan berpikir formal untuk siswa kelas eksperimen untuk indikator berpikir hipotesis deduktif, berpikir kombinasi dan refleksi berada pada kategori sedang, berpikir proporsional pada kategori tinggi. Untuk siswa kelas kontrol perentase N-gain rata-rata untuk berpikir hipotesis deduktif  berada pada kategori rendah, sementara berpikir proporsional, berpikir kombinasi dan berpikir refleksi berada pada kategori sedang.